Prevention of Bullying and Sexual Violence Through Moral Education at Miftahul Ulum Islamic Boarding School - Kasdi Tri Aryada; Didik Muhammad Nur Haris; Baidhillah Riyadhi; Farida Asy’ari; Liliyana; Riska Wahyuni; Mujib; Agus Susanto; Grace Kelly Hedi Putri Sihombing; Mery Lestari (Civitas : Jurnal Pengabdian Masyarakat, 2026)
The PKM program conducted by the team of lecturers who are members of MKWK Polnep in 2025 is entitled “Prevention of Bullying and Sexual Violence through Moral Education at the Miftahul Ulum Islamic Boarding School” in Sungai Raya District, Kubu Raya Regency. The background of the PKM implementation is part of the tri dharma of higher education in addressing the rampant cases of bullying and sexual violence that occur in educational environments, including Islamic boarding schools, where the victims are school-age children. Therefore, the purpose of this activity is to provide knowledge to students, teachers, and educational staff on the importance of knowing the boundaries that violate acts of bullying and sexual violence through the instillation of morality based on the values of Pancasila and Civic Education, as well as to strive to form a task force for the prevention and handling of violence at the Miftahul Ulum Islamic Boarding School, which has not yet been formed. To that end, the method used is socialization followed by knowledge about morality, involving students, teachers, and educational staff to learn about the importance of moral values based on religious values, Pancasila, and civic education and social culture so that after the PKM is implemented, participants can apply it in their social interactions. The results of this activity show that: 1) the number of participants was in line with the target of 100 people, 2) no participants left or entered the room and all listened attentively, 3) participants actively participated in the activity by asking questions, 4) participants were able to answer the post-test questions given by the presenter.